Analisis Kondisi Status Sosial Ekonomi Keluarga Dalam Menunjang Pemenuhan Kebutuhan Pendidikan Anak: Status Sosial - Eviana Hikamudin; Hasan Bisri; Rahman Wahid (Edusifa: Jurnal Pendidikan Islam, 2023)
Education is an urgent and necessary thing for every individual. As for children, education is a basic need that will support the development of children's mindset, character, and skills. Meeting the educational needs of children is the responsibility of the family, especially parents because the family is the primary and first educational institution for a child. However, in meeting children's educational needs, the condition of the family's socioeconomic status can become a problem in itself. The method used in this research is library research. The study aims to describe the condition of the family's socioeconomic status in supporting the fulfillment of children's education. The results of the study show that the socioeconomic status of the family can have an impact on meeting the educational needs of children.